Cardiac implantable electronic device infections: prognostic value of the PADIT score and its cost-utility implications for antimicrobial envelope use in the United Kingdom. (3rd October 2022) - Mahtani, K; Maclean, E; Honarbakhsh, S; Bhuva, A; Finlay, M; Creta, A; Earley, M J; Zemrak, F; Moore, P; Muthumala, A; Sporton, S; Schilling, R J; et al.
Abstract: Background: The incidence of cardiac implantable electronic device (CIED) infections is rising. Purpose: We examined the factors associated with CIED infection, assessed the prognostic power of the PADIT risk score, and modelled the cost-utility of selective TYRX antimicrobial envelope use for preventing CIED infections. Methods: Data were extracted from 2016 to 2019, and included all de novo implants, generator changes and lead interventions for transvenous CIEDs at a high-volume UK centre. CIED infection was defined as hospitalisation for device infection within 12 months of a procedure. Cost-utility analysis was informed by standardised tariffs, and quality adjusted life year (QALY) and efficacy data was extrapolated from analysis of the WRAP-IT trial. Results: 6, 035 patients underwent 7, 383 procedures; CIED infection occurred in 59 individuals (0.8%). In addition to the constituents of the PADIT score, lead extraction (HR 3.3 (1.9–6.1), p<0.0001), C-reactive protein >50mg/l (HR 3.0 (1.4–6.4), p=0.005), re-intervention within two years (HR 10.1 (5.6–17.9), p<0.0001), and procedure duration over two hours (HR 2.6 (1.6–4.1), p=0.001) were independent predictors of infection. Increased PADIT score was strongly associated with infection (AUC: 0.82, HR per point increase: 1.36 (1.27–1.47), p<0.0001). A cost-utility model assigning TYRX envelopes to patients with PADIT scores ≥6 predicted a reduction in infections (number needed to treat: 72) and a cost per QALY gained within the UK's (NICE) cost-effectiveness threshold (£25, 107). Conclusions: The PADIT score was a powerful predictor of CIED infections in a heterogeneous population, and may facilitate cost-effective TYRX envelope allocation in selected high-risk patients. Funding Acknowledgement: Type of funding sources: None.